2005
DOI: 10.2131/jts.30.329
|View full text |Cite
|
Sign up to set email alerts
|

Paired Acute Inhalation Test Reveals That Acetaldehyde Toxicity Is Higher in Aldehyde Dehydrogenase 2 Knockout Mice Than in Wild-Type Mice

Abstract: -Aldehyde dehydrogenase 2 (ALDH2) is an important enzyme that oxidizes acetaldehyde.Approximately 45% of Chinese and Japanese individuals have the inactive ALDH2 genotypes (ALDH2*2/ *2 and ALDH2*1/*2); acute inhalation toxicity of acetaldehyde has not been evaluated in these populations. We compared the toxicity between wild-type (Aldh2+/+) and Aldh2-inactive transgenic (Aldh2−/−) mice by using the paired acute inhalation test modified from the acute toxic class method (OECD TG433). Blood acetaldehyde level wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Exposure to acetaldehyde is not only due to ethanol consumption but also due to the use of acetylaldehyde in industrial and household materials (Isse et al 2005b). Oyama et al (2007a) reported inhalation toxicity of acetaldehyde in Aldh2 knockout mice.…”
Section: Acute Inhalation Toxicity Of Acetaldehyde In Aldh2 Knockout mentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to acetaldehyde is not only due to ethanol consumption but also due to the use of acetylaldehyde in industrial and household materials (Isse et al 2005b). Oyama et al (2007a) reported inhalation toxicity of acetaldehyde in Aldh2 knockout mice.…”
Section: Acute Inhalation Toxicity Of Acetaldehyde In Aldh2 Knockout mentioning
confidence: 99%
“…Acetaldehyde is widely produced as an intermediary product of alcohol, acetic acid, certain esters, and a number of other chemicals in ethylene and alcohol fermentation plants; it is also present in tobacco smoke (IPCS 1995;Isse et al 2005b). Acetaldehyde is rapidly metabolized to acetic acid by aldehyde dehydrogenase (ALDH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been little evidence as to whether the toxic effect is different according to the activity of the Aldh2 enzyme (Isse et al, 2005a(Isse et al, , 2005b(Isse et al, , 2005cOyama et al, 2005), which is a major enzyme in ethanol metabolism. In this study, the weights of the mice were decreased to 85% and 74% of the control Aldh2 +/+ and Aldh2 −/− group, respectively, when ethanol was administered.…”
Section: Discussionmentioning
confidence: 99%
“…Aldh2 −/− mice were maintained with a C57BL/6 strain and backcrossed with C57BL/6 strain for more than 10 generations for the experiments at the animal center of University of Occupational and Environmental Hearth (UOEH) (The Jackson laboratory mouse genome informatics # 99600 ) (Isse et al, 2005b). These mice were housed in specific pathogen-free units of the Division of Animal Care at the University of Occupational and Environmental Health.…”
Section: Methodsmentioning
confidence: 99%